2022
DOI: 10.1021/jacs.2c06985
|View full text |Cite
|
Sign up to set email alerts
|

Solution Deposition for Chalcogenide Perovskites: A Low-Temperature Route to BaMS3 Materials (M = Ti, Zr, Hf)

Abstract: Chalcogenide perovskites, including BaZrS3, have been suggested as highly stable alternatives to halide perovskites. However, the synthesis of chalcogenide perovskites has proven to be a significant challenge, often relying on excessively high temperatures and methods that are incompatible with device integration. In this study, we developed a solution-based approach to the deposition of BaZrS3. This method utilizes a combination of a soluble barium thiolate and nanoparticulate zirconium hydride. Following sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 33 publications
(63 reference statements)
3
46
0
1
Order By: Relevance
“…Additionally, sharper photoluminescence has been obtained for BaHfS 3 compared to BaZrS 3 . [ 18 ] As BaHfS 3 also contains barium and sulfur, a liquid BaS x flux should also be applicable to its synthesis. While early reports on the synthesis of BaHfS 3 using binary sulfides utilized a temperature of 1100 °C for 48 h, [ 11 ] we observed that adding excess sulfur to powder precursors BaS and HfS 2 such that the Ba:Hf:S mole ratio is 1:1:9 brought the reaction conditions down to 575 °C and 12 h ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, sharper photoluminescence has been obtained for BaHfS 3 compared to BaZrS 3 . [ 18 ] As BaHfS 3 also contains barium and sulfur, a liquid BaS x flux should also be applicable to its synthesis. While early reports on the synthesis of BaHfS 3 using binary sulfides utilized a temperature of 1100 °C for 48 h, [ 11 ] we observed that adding excess sulfur to powder precursors BaS and HfS 2 such that the Ba:Hf:S mole ratio is 1:1:9 brought the reaction conditions down to 575 °C and 12 h ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Our group recently developed a direct‐to‐film solution‐processed route for BaMS 3 (M = Ti, Zr, Hf) materials that utilizes heat treatment in a sulfur‐containing atmosphere at modest temperatures from 500 to 575 °C. [ 18 ] For the case of BaZrS 3 , large grains on the order of hundreds of nanometers were obtained, which is desirable for applications in thin‐film photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated above, solution‐based synthesis of a large number of multinary chalcogenides, especially those based on Group 11–15 elements, are available [37, 49, 50] . However, until recently, solution‐based synthesis of multinary AMS 3 (A=Ca, Sr, Ba; M=Ti, Zr, Hf) compounds has been missing from the literature [46–48, 58] . Creutz Group reported an early synthesis of non‐perovskite BaTiS 3 nanorods using dithiocarbamate complexes of Ba and Ti in oleylamine [58] .…”
Section: Methodsmentioning
confidence: 99%
“…[36] c. Chemical formular of the nanoparticle synthesis with DBuDTC. [37] 이재욱, 양우석 태로 기판 위에 도포하는 것에 성공하였다 [38] . 이 연구에…”
Section: Iodine 촉매 활용 고체상 반응법unclassified